The Effect of Organizational Culture and Job Satisfaction on Work Motivation of Industry and Trade Service Employees in Sungai Penuh City - Efrianto, Efrianto; Hendra, Hendra; Kartawijaya, Sukarta (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
A factor that cannot be ignored in improving employee performance is motivation. This is according to Hasibuan's opinion (1996: 45) an employee will produce performance high if employees are motivated at work. Motivation can be a driving force someone carries out an activity in order to get the best results. Therefore it is not surprising that employees who have high work motivation usually also have high performance. Another factor which cannot be ignored Improving employee performance is an "organizational culture", a culture that is getting better organization that is implemented in an institution, the more enthusiasm will also increase employee work, because basically organizational culture is a rule that bind employees to organize and act according to the rules that have been set and agreed together. The purpose of this study is to determine the influence of motivation work and organizational culture on employee performance at the Department of Industry and Sungai Penuh City Trade. The data collection techniques in this study are observation, interview, questionnaire. The sample in this study were 60 people employee at the Department of Industry and Commerce City of Sungai Penuh. In this study the authors used qualitative and quantitative data analysis. In general the results of this research are as follows:. 1) There is a positive influence between motivation work on the performance of employees at the Department of Industry and Trade of the City of Sungai Penuh. 2) There is a positive influence between organizational culture on employee performance at the Office of Industry and Trade of Sungai Penuh City 3) work motivation and organizational culture jointly has a positive effect on employee performance at the Department of Industry and Trade of Sungai Penuh City.